Analysis of Cost Budget and Cost Budget Realization Before and During the Covid-19 Pandemic at Hotel XYZ - Rani Nursyifa; Dianila Oktyawati (JFBA: Journal of Financial and Behavioural Accounting, 2021)
This study was conducted at Hotel XYZ, which is a tourism-related services company. This study aims to determine whether the realization of Hotel XYZ's cost budget before and during the Covid-19 pandemic was effective and efficient. The data used is operational data from Hotel XYZ in 2019 and 2020, supported by information derived from interviews with Hotel XYZ's chief accounting officer. The method is the qualitative descriptive analysis. The technique used for data analysis is the analysis of variance. The results showed that the realization of Hotel XYZ's cost budget before and during the Covid-19 pandemic was effective and efficient.